Forced expression of muscle specific kinase slows postsynaptic acetylcholine receptor loss in a mouse model of MuSK myasthenia gravis. Issue 12 (23rd December 2015) - Ghazanfari, Nazanin; Linsao, Erna L. T. B.; Trajanovska, Sofie; Morsch, Marco; Gregorevic, Paul; Liang, Simon X.; Reddel, Stephen W.; Phillips, William D.
Abstract: We investigated the influence of postsynaptic tyrosine kinase signaling in a mouse model of muscle‐specific kinase (MuSK) myasthenia gravis (MG). Mice administered repeated daily injections of IgG from MuSK MG patients developed impaired neuromuscular transmission due to progressive loss of acetylcholine receptor (AChR) from the postsynaptic membrane of the neuromuscular junction. In this model, anti‐MuSK‐positive IgG caused a reduction in motor endplate immunolabeling for phosphorylated Src‐Y418 and AChR β ‐subunit‐Y390 before any detectable loss of MuSK or AChR from the endplate. Adeno‐associated viral vector (rAAV) encoding MuSK fused to enhanced green fluorescent protein (MuSK‐EGFP) was injected into the tibialis anterior muscle to increase MuSK synthesis. When mice were subsequently challenged with 11 daily injections of IgG from MuSK MG patients, endplates expressing MuSK‐EGFP retained more MuSK and AChR than endplates of contralateral muscles administered empty vector. Recordings of compound muscle action potentials from myasthenic mice revealed less impairment of neuromuscular transmission in muscles that had been injected with rAAV‐MuSK‐EGFP than contralateral muscles (empty rAAV controls). In contrast to the effects of MuSK‐EGFP, forced expression of rapsyn‐EGFP provided no such protection to endplate AChR when mice were subsequently challenged with MuSK MG IgG. In summary, the immediate in vivo effect of MuSK autoantibodies was to suppress MuSK‐dependent tyrosine phosphorylation of proteins in the postsynaptic membrane, while increased MuSK synthesis protected endplates against AChR loss. These results support the hypothesis that reduced MuSK kinase signaling initiates the progressive disassembly of the postsynaptic membrane scaffold in this mouse model of MuSK MG. Abstract : Autoimmune antibodies against Muscle Specific Kinase (MuSK) are thought to cause some cases of myasthenia gravis. The pathogenic effects of these antibodies on the mouse neuromuscular junction were ameliorated by supplementing the expression of MuSK. This confirms that MuSK autoantibodies cause myasthenia gravis by impairing MuSK function.